2011
DOI: 10.3892/etm.2011.394
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumor effects of a dendritic cell vaccine transfected with gastric cancer cell total RNA carrying the 4-1BBL gene in vitro

Abstract: Abstract. T cell-mediated antitumor immunity is a cellular immune response that requires two signals. The dendritic cell (DC) has been considered as the most efficient antigen-presenting cell (APC). It plays essential roles in the induction, regulation and maintenance of antitumor immunity in humans. The 4-1BB/4-1BB ligand (4-1BBL) pathway plays crucial roles in immune response, tumor immunity and autoimmune diseases through transduction of T cell co-stimulatory signals. The aim of this study was to generate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In this regard, conversion of MDSCs toward a proinflammatory phenotype by IND treatment may boost DC vaccination protocols and cooperate with other immunotherapeutic regimens (1). Furthermore, IND treatment of tumor-bearing hosts may limit MDSC function and stimulate tumor immunity in an Ag-independent manner which avoids studies of the patient´s HLA phenotype, a problem that is frequently faced in DC or peptide vaccination protocols (38). Interestingly, in an experimental model of mouse breast cancer metastasis, IND was able to restore the anti-metastatic effect of adoptively transferred macrophages, thus supporting the effects of this drug on other tumor-associated myeloid cell populations (39).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, conversion of MDSCs toward a proinflammatory phenotype by IND treatment may boost DC vaccination protocols and cooperate with other immunotherapeutic regimens (1). Furthermore, IND treatment of tumor-bearing hosts may limit MDSC function and stimulate tumor immunity in an Ag-independent manner which avoids studies of the patient´s HLA phenotype, a problem that is frequently faced in DC or peptide vaccination protocols (38). Interestingly, in an experimental model of mouse breast cancer metastasis, IND was able to restore the anti-metastatic effect of adoptively transferred macrophages, thus supporting the effects of this drug on other tumor-associated myeloid cell populations (39).…”
Section: Discussionmentioning
confidence: 99%
“…DCs based anti tumor immunotherapy have strong ability to stimulate naïve T lymphocytes and induce effective anti-tumor responses (Guermonprez et al, 2002). There were many reports on DC vaccine in the treatment of melanoma, ovarian, colon, breast and gastric cancer (Song et al, 2012). Another study showed that dendritic cells pulsed with lung cancer cell lysate could induce tumor specific immune response and showed promising clinical outcomes in patient with lung cancer (Han et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…They play a vital role in the initiation of immune response by presenting exogenous and endogenous antigens to T-cells via major histocompatibility complex molecules (Ragde et al, 2004). Following induction of the T-cell response, the activated T cells can differentiate into cytotoxic T lymphocytes (Song et al, 2012). CTL are the major killers of tumor cells, they achieve the killing with the help of CD4+ T cells, which cans induce potential long-termCD8+ T-cell responses by producing various cytokines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tumor bearing mice, intratumoral OX-40 activation increases CD40 expression on T cells and increases the effector memory T cells (T EM ) subset [ 34 ]. 4-1BBL (TNFRSF9/CD137) costimulation of tumor-specific T cells is important for T-cell activation and 4-1BBL transfected DCs elicit more effective responses and enhanced CTL killing of tumor cells, due to increased expression of perforin and IFN-γ [ 35 ]. In recognition of the importance of these pathways to generating effective antitumor immunity, clinical studies have started to evaluate the effectiveness of humanized agonist antibodies to both OX-40 and 4-1BB [ 36 39 ].…”
Section: Introductionmentioning
confidence: 99%